Physical Exercise and Its Protective Effects on Diabetic Cardiomyopathy: What Is the Evidence? - Zheng, Jia; Cheng, Jing; Zheng, Sheng; Zhang, Ling; Guo, Xiaohui; Zhang, Junqing; Xiao, Xinhua (Frontiers in Endocrinology, 2018)
As one of the most serious complications of diabetes, diabetic cardiomyopathy (DCM) imposes a huge burden on individuals and society, and represents a major public health problem. It has long been recognized that exercise has important health benefits for people with type 2 diabetes, and regular physical exercise can delay or prevent the onset of diabetes and DCM. Current studies show that physical exercise has been regarded as an importantly non-pharmacological treatment for diabetes and DCM with high efficacy and low adverse events. It can inhibit the pathological processes of myocardial apoptosis, myocardial fibrosis, and myocardial microvascular diseases through improving myocardial metabolism, enhancing the regulation of Ca2+, and protecting the function of mitochondria, and eventually, it can alleviate the occurrence and development of diabetic complications. Describing the mechanisms of exercise on diabetic myocardium may provide a new theory for alleviating, or even reversing the development of DCM, and prevent it from developing to heart failure.